Heart Transplantation for Chagas Cardiomyopathy in the United States. Issue 12 (28th October 2013) - Kransdorf, E. P.; Czer, L. S. C.; Luthringer, D. J.; Patel, J. K.; Montgomery, S. P.; Velleca, A.; Mirocha, J.; Zakowski, P. C.; Zabner, R.; Gaultier, C. R.; Qvarnstrom, Y.; Benedict, T.; et al.
Abstract Since an initial case in 2006, we noted multiple patients undergoing heart transplantation (HTx) for Chagas cardiomyopathy (CC) at our transplant program. The clinical characteristics, laboratory results and outcomes of patients with CC undergoing HTx in the United States have not been reported previously. In 2010, we implemented a systematic screening and management program for patients undergoing HTx for CC. Before HTx, all patients with idiopathic dilated cardiomyopathy who were born in a Chagas disease endemic country were screened for Trypanosoma cruzi (TC) infection with serology. After HTx, monitoring for TC reactivation was performed using clinical visits, echocardiography, endomyocardial biopsy and serial whole blood polymerase chain reaction (PCR) testing. Between June 2006 and January 2012, 11 patients underwent HTx for CC. One patient was empirically treated due to the presence of TC amastigotes in explanted cardiac tissue. Two patients experienced allograft dysfunction due to TC reactivation and three patients experienced subclinical reactivation (positive PCR results), which were treated. Chagas disease is a common cause of dilated cardiomyopathy in patients from endemic countries undergoing HTx at a transplant program in the United States. Reactivation is common after transplantation and can cause adverse outcomes.